The effectiveness of psychosocial services in Albania - Kavaja, Uarda; Demaj, Era; Begotaraj, Edvaldo (Optime, 2025)
In 2025, psychosocial services in Albania are undergoing a process of continuous development, driven by the growing needs of society and efforts to align with European standards of social welfare. These services play a fundamental role in supporting individuals facing emotional, psychological, and social difficulties; therefore, assessing their effectiveness is essential for designing sustainable and evidence-informed social policies. In this context, digitalisation represents an important opportu- nity to improve both access to and the quality of psychosocial services. Albania has made significant progress in the digitalisation of public administration and social services; however, the integration of digital components into psychosocial care provision remains fragmented and uneven This study examines the effectiveness of psychosocial services at the national level, with a particular focus on access, quality, digitalisation, and the extent to which interventions respond to the needs of diverse social groups. The research draws on data collected from public institutions, non-govern - mental organisations, field experts, and case studies. The analysis assesses institutional capacities, staff professional preparedness, the adoption of digital technologies, and service users’ perceptions regarding the impact and quality of the psychosocial support provided. The findings indicate mod- erate improvements in urban areas, particularly where online platforms have been implemented for counselling and psychosocial assistance, while substantial challenges persist in rural and marginal - ised communities. These challenges include limited access to technological resources, weak interin - stitutional coordination, and social stigma associated with seeking help. The recommendations highlight the need for a clear national strategy for the digitalisation of psycho- social services, stronger intersectoral collaboration, greater investment in professional education and supervision, and the strengthening of monitoring and evaluation mechanisms, including the use of digital tools. The study aims to contribute to the development of a more effective, inclusive, and con- text-sensitive service system, aligned with Albania’s European integration process and the country’s broader digital transformation agenda.